2020
DOI: 10.3389/fnins.2020.00215
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA Let-7i Is a Promising Serum Biomarker for Post-stroke Cognitive Impairment and Alleviated OGD-Induced Cell Damage in vitro by Regulating Bcl-2

Abstract: Background: The mechanism of post-stroke cognitive impairment (PSCI) has not been explained. We aimed to investigate whether miR-let-7i participates in the PSCI and illuminates its underlying role in oxygen-glucose deprivation (OGD)-induced cell apoptosis.Methods: Blood samples from 36 subjects with PSCI and 38 with post-stroke cognitive normality (Non-PSCI) were collected to evaluate the differential expression of miRlet-7 family members, using qRT-PCT analysis. Spearman correlation was performed to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus, the increased abundance of Enterobacteriaceae might be significantly associated with PSCI.Due to the severity of PSCI, it is urgent to find biomarkers for PSCI diagnosis. Previous studies demonstrated that some microRNAs could achieve expected results in the diagnosis of PSCI (Huang et al, 2016;Wang et al, 2020). Besides, recent studies indicated that the imaging and multiple cellular changes had made significant progress in the diagnosis of neurological disease (Vijayan and Reddy, 2016a;Eyileten et al, 2018;Guo et al, 2018;Vijayan et al, 2018;Saba et al, 2019).…”
Section: Figure 3 |mentioning
confidence: 99%
“…Thus, the increased abundance of Enterobacteriaceae might be significantly associated with PSCI.Due to the severity of PSCI, it is urgent to find biomarkers for PSCI diagnosis. Previous studies demonstrated that some microRNAs could achieve expected results in the diagnosis of PSCI (Huang et al, 2016;Wang et al, 2020). Besides, recent studies indicated that the imaging and multiple cellular changes had made significant progress in the diagnosis of neurological disease (Vijayan and Reddy, 2016a;Eyileten et al, 2018;Guo et al, 2018;Vijayan et al, 2018;Saba et al, 2019).…”
Section: Figure 3 |mentioning
confidence: 99%
“…MMSE score was used to define cognitive recovery in one study at 14 days after stroke [58], whereas MoCA score assessed cognitive impairments in three studies in the chronic phase of stroke patients (within 1 year) [50,51,55]. To measure depression symptoms among post-stroke patients, three studies evaluated HAMD scores within 2-3 weeks and at 3 months after stroke onset [99][100][101].…”
Section: Prognostic Tools and Prediction Of Physical Recovery In Is P...mentioning
confidence: 99%
“…A total of 13 studies performed ROC analyses to analyze the prognosis of IS patients (neurological deficit severity and post-stroke disability) of the 15 circulating biomarkers. Of the 15 differentially expressed miRNAs, five miRNAs (miR-132, let-7i, miR-140-5p, miR-22, and miR-221-3p) [50,55,[99][100][101] were upregulated in patients with cognitive impairments after stroke, and 12 miRNAs (miR-24, miR-29b, miR-210, miR-411-5p, miR-124-3p, miR-125b-5p, miR-192-5p, miR-210, miR-185, miR-424, miR-100-5p, and miR-210) [53,61,62,75,82,87,90,102] were downregulated in poor-prognosis patients with motor deficits.…”
Section: Clinical Utility Of Mirna-based Biomarkers In Prediction Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Exosome-derived miR-let-7c promotes angiogenesis in multiple myeloma by polarizing macrophages. 18 Moreover, miR-let-7i-5p is a promising serum biomarker for poststroke cognitive impairment and alleviated oxygen glucose deprivation-induced cell damage in vitro by regulating Bcl-2 19 and involved in inflammation associated cells apoptosis. 20 Here, we aim to investigate the relationship among exosomal miR-let-7c-5p (or miR-let-7i-5p), IL-10 levels in plasma, and MCI in type 2 diabetes mellitus (T2DM) patients via the present cross-sectional research.…”
Section: Introductionmentioning
confidence: 99%